Independence of geostatic stress from overconsolidation in some Beaufort Sea clays - Jefferies, M. G.; Crooks, J. H. A.; Becker, D. E.; Hill, P. R. (Canadian Geotechnical Journal, 1987)
Since 1982, extensive use has been made of the self-bored pressuremeter in Arctic offshore site investigations. One finding of this work is that the in situ geostatic stress ratio K 0 of Beaufort Sea clays is apparently unrelated to the overconsolidation ratio (OCR). The procedures and data to support this finding are documented and the finding is discussed in light of the present geological understanding for the area. It is concluded that the independence of K 0 from OCR may be quite widespread, a finding that contradicts the widely held tenet regarding the existence of a single-valued function relating K 0 , [Formula: see text], and OCR. If K 0 is regarded as important, then it should be measured in situ. Key words: self-bored pressuremeter, geostatic stress ratio (K 0 ), Beaufort Shelf, geologic history, overconsolidation ratio.